Physical model simulation of block caving in jointed rock mass - Behnam Alipenhani; Hassan Bakhshandeh Amnieh; Abbas Majdi (International Journal of Mining and Geo-Engineering, 2022)
Incorrect estimation of undercut dimensions in the block caving method can lead to the cessation of caving operations and loss of a large portion of deposits. Numerical modeling is one of the methods for determining the minimum caving span. Numerical and physical modeling methods are useful for an accurate understanding of caving operations. Accordingly, this research focused on investigating the performance of physical and numerical modeling in determining the effects of depth and joint orientation on the minimum required caving span for the initiation and propagation of caving. The physical model was made with 1.5*1.5 square meter dimensions and consisted of travertine blocks with 4*4 square centimeter dimensions. In addition, joints were modeled with dips of 0, 90, 45, 135, 30, and 120 degrees. The physical model could simulate ground stress conditions to great depths and show the behavior of the jointed rock mass in a two-dimensional space. Further, by capturing this behavior, it was possible to compare its result with UDEC software. The results demonstrated that the number of falling blocks and the height of the caving increased by increasing the dip. Furthermore, the formation of arches due to high horizontal stress stops the caving, which will occur again with the increasing span. Although the horizontal stresses and geometrical properties of the joints affect the shape of the caving area, its shape largely follows the dip and orientation of the rock mass joints. Poor draw control causes caved ore columns, which can lead to the formation of a stable arc. Finally, the height of the caved back increases in each span by increasing the depth while decreasing the dip of the joints.